Impact of Hydroxyurea on Blood Transfusions and Its Safety in β-Thalassemia patients - Malik Asif Hussain, Ayesha Asif, Usama Gorsi, Aamir Mushatq, Umar Farooq Gohar, Asad Iftikhar Shah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Thalassemia is a genetic defect characterized by abnormal hemoglobin in red blood cells and resultant anemia. Currently, regular blood transfusion or fetal hemoglobin inducers or a combination of these is clinically used to manage these patients. Aim: To observe effectiveness of Hydroxyurea in β-Thalassemia patients, particularly focusing on change in frequency of blood transfusions. Methods: This study analyzed data of the patients registered with thalassemia society of Pakistan and Sundas Foundation of district Lahore, Punjab, Pakistan. Eighty seven patients were selected for analysis based on available data and specific inclusion criteria. The results were calculated using “dependent/paired sample t test” and presented in form of graphs. Results: Out of eighty seven patients, 72 % of the patients were diagnosed with thalassemia major, 26% with thalassemia intermedia and 1% with thalassemia minor. Additional analysis showed more cases in males (57 %); dominance of cases in cousin marriages (87 %) and majority of patients were 1-10 years (60 %) old. In this study, the impact of hydroxyurea was observed on reduction of blood transfusions in thalassemia patients. Overall, 11.5% patients showed excellent response, 65.5 % were good responders and 25% patients did not show clinical improvement with hydroxyurea use. The dosage of hydroxyurea was based on weight of the patients. Conclusions: It is hence concluded that Hydroxyurea is safe and effective drug for thalassemia patients, as it reduces the blood transfusion need of the patients and help to improve their quality of life. Keywords: Blood transfusion, Anemia, Hydroxyurea, Thalassemia.